Application of a lattice Boltzmann method to some challenges related to micro-air vehicles. Issue 3 (September 2018) - Gourdain, Nicolas; Jardin, Thierry; Serre, Ronan; Prothin, Sébastien; Moschetta, Jean-Marc
The demand for micro-air vehicles is increasing as well as their potential missions. Whether for discretion in military operations or noise pollution in civilian use, the improvement of aerodynamic and acoustic performance of micro-air vehicles propeller is a goal to achieve. Micro- and nano-air vehicles operate at Reynolds numbers ranging from 10 3 to 10 5 . In these conditions, the aerodynamic performance of conventional fixed and rotary wings concepts drastically decreases due to the increased importance of flow viscous forces that tend to increase drag and promote flow separation, which leads to reduced efficiency and reduced maximum achievable lift. Reduced efficiency and lift result in low endurance and limited payloads. The numerical simulation is a potential solution to better understand such low Reynolds number flows and to increase the micro-air vehicles' performance. In this paper, it is proposed to review some challenges related to micro-air vehicles by using a Lattice-Boltzmann method. The method is first briefly presented, to point out its strengths and weaknesses. Lattice-Boltzmann method is then applied to three different applications: a DNS of a single blade rotor, a large eddy simulation of a rotor operating in-ground effect and a large eddy simulation of a rotor optimised for acoustic performance. A comparison with reference data (Reynolds Averaged Navier-Stokes, DNS or experimental data) is systematically done to assess the accuracy of lattice-Boltzmann method-based predictions. The analysis of results demonstrates that lattice-Boltzmann method has a good potential to predict the mean aerodynamic performance (torque and thrust) if the grid resolution is chosen adequately (which is not always possible due to limited computational resources). A study of the turbulent flow is conducted for each application in order to highlight some of the physical flow phenomena that take place in such rotors. Different designs are also investigated, showing that potential improvements are still possible in terms of aerodynamic and aero-acoustic performance of low-Reynolds rotors.